Methodological approach in the development of the cognitive-volitional component of e-sportsmans - Kosmina E.A. ,; Makarov Yu.M. ,; Shubin K.Yu. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to justification for the use of a scientific and methodological approach in the development of the cognitive-volitional component of cybersportsmen. Methods and structure of the study. The development of the cognitive-volitional component was carried out within the framework of integral training, based on the developed scientific and methodological approach. The experiment, which lasted 18 months, involved 52 e-sportsmen aged 18-25. Control testing of the level of cognitive-volitional indicators of the subjects was carried out every six months according to the following indicators: index of volitional self-regulation, perseverance, self-control, cognitive errors in sports based on situational awareness, awareness, control. Results and conclusions. The use of a scientific and methodological approach in the educational and training process of e-sportsmen involved in various disciplines of computer sports makes it possible to increase the level of development of the cognitive-volitional component, which is confirmed by experimental studies. During the experiment, the level of volitional self-regulation of those involved in various disciplines of computer sports increased to 12,3%, self-control – to 10,8%, perseverance – to 15,5%, the number of cognitive errors decreased, based on situationality – to 20,4%, awareness – up to 23,4%, control – 28,7%.